Serologic Testing of US Blood Donations to Identify Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2)–Reactive Antibodies: December 2019–January 2020. (30th November 2020) - Basavaraju, Sridhar V; Patton, Monica E; Grimm, Kacie; Rasheed, Mohammed Ata Ur; Lester, Sandra; Mills, Lisa; Stumpf, Megan; Freeman, Brandi; Tamin, Azaibi; Harcourt, Jennifer; Schiffer, Jarad; Semenova, Vera; et al.
Abstract: Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the virus that causes coronavirus disease 2019 (COVID-19), was first identified in Wuhan, China, in December 2019, with subsequent worldwide spread. The first US cases were identified in January 2020. Methods: To determine if SARS-CoV-2–reactive antibodies were present in sera prior to the first identified case in the United States on 19 January 2020, residual archived samples from 7389 routine blood donations collected by the American Red Cross from 13 December 2019 to 17 January 2020 from donors resident in 9 states (California, Connecticut, Iowa, Massachusetts, Michigan, Oregon, Rhode Island, Washington, and Wisconsin) were tested at the Centers for Disease Control and Prevention for anti–SARS-CoV-2 antibodies. Specimens reactive by pan-immunoglobulin (pan-Ig) enzyme-linked immunosorbent assay (ELISA) against the full spike protein were tested by IgG and IgM ELISAs, microneutralization test, Ortho total Ig S1 ELISA, and receptor-binding domain/ACE2 blocking activity assay. Results: Of the 7389 samples, 106 were reactive by pan-Ig. Of these 106 specimens, 90 were available for further testing. Eighty-four of 90 had neutralizing activity, 1 had S1 binding activity, and 1 had receptor-binding domain/ACE2 blocking activity >50%, suggesting the presence of anti–SARS-CoV-2–reactive antibodies. Donations with reactivity occurred in all 9 states. Conclusions: These findings suggest that SARS-CoV-2 may have been introduced into the United States prior to 19 January 2020. Abstract : Retrospective SARS-CoV-2 serological testing of routine blood donations collected in 9 US states from 13 December 2019–17 January 2020 suggests that the virus was present in the United States earlier than previously recognized.